RANCANG BANGUN MESIN PENCACAH SABUT KELAPA MENJADI SERBUK KELAPA (COCOPEAT) - Irwandi, Muhammad; Setyawan, Riko; Tarman, Tarman; Sugianto, Sugianto; Hasdiansah, Hasdiansah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
This study aims to design a portable coconut husk shredding machine capable of producing cocopeat, with an emphasis on ease of operation and mobility. The machine is powered by a 7.5 HP gasoline engine and utilizes a shredding system composed of four cutting blades and ten beaters to break down coconut husks into fine cocopeat particles. The design process follows the systematic VDI 2222 method, which includes need identification, concept development, and selection of the final design. The main focus is to create a compact, lightweight, and easily transportable structure without compromising shredding performance. The resulting design successfully meets the operational needs of field users, particularly in terms of portability and user-friendliness. This project was conducted in Bangka Belitung in 2025.